Trait emotional intelligence and disposition for forgiveness - Daniela Carvalho (2010)
The association of trait emotional intelligence with a disposition for forgiveness was explored. In addition, the relationship between emotional intelligence and affect was also examined. A sample of 268 Portuguese students completed measures of trait emotional intelligence, disposition to forgive, and affect. Results demonstrated that trait emotional intelligence scores were negatively associated with lasting resentment and negative affect and positively associated with positive affect.